Wichtigste Kontaktallergene beim Handekzem - Mahler, Vera; Dickel, H. (Hautarzt, 2019)
The head and hands are the two most common locations for allergic contact dermatitis manifestation. In hand eczema, contact with a contact allergen is a frequent (co-)factor in the triggering and maintenance of eczema. For all hand eczemas lasting longer than 3 months, an allergological examination by means of patch testing is recommended. In patients with allergic contact dermatitis of the hands, nickel, MCI/MI, fragrance mix I, cobalt, thiuram mix, Balsam of Peru, chromium and fragrance mix II have been described in a multicenter European study as the most common contact allergens of the standard series. In the information network of dermatological clinics (IVDK) a total of 56,170 patients were patch-tested in the years 2014 to 2018. In all, 16,807 of these patients (29.9%) suffered from hand eczema, of which 7725 (46.0%) had occupational dermatosis (OD) and 6820 (40.6%) had no OD. For the remaining patients this was unknown. The top 30-list of allergens in hand eczema patients without and with OD included 22 common contact allergens, but with different reaction frequency. In hand eczema patients without OD, the following contact allergens also belong to this list: octyl gallate, sorbic acid, tert-butylhydroquinone, propylene glycol, mercury (II) amide chloride, tolubalsam, jasmine absolute, and sandalwood oil. For hand eczema patients with OD, these are instead: tetramethylthiurammonosulfide, tetramethylthiuramdisulfide, 1,3-diphenylguanidine, p‑phenylenediamine, p‑toluylenediamine, iodopropinylbutylcarbamate, glutaraldehyde, and monoethanolamine. In the case of OD of the hands, early involvement of the responsible statutory accident insurance by initiating the dermatologist procedure ("Hautarztverfahren") is necessary in order to work together towards successful allergen avoidance by means of substitution and optimizing personal protective equiment.
CRIS-Team Scopus Importer:2019-10-04
Keywords: Allergen avoidance; Allergen top charts; Dermatologist procedure; Occupational dermatosis; Patch tests